2-acetylthiophene thiosemicarbazone as mushroom tyrosinase inhibitor: insights from kinetic, RDG, molecular docking, and DFT studies - Ahmad, Mohammad Norazmi; Jori Roslan, Muhammad Qusyairi; Abdullah, Erna Normaya (2019)
The pressing need for better drugs against skin pigmentation motivates the search for inhibitors of tyrosinase enzyme, the main causative agent.Tyrosinase (EC 1.14.18.1), which is a copper-containing enzyme, plays a vital role in preventing skinpigmentation due to melanin biosynthesis. In this study, we have synthesized 2-acetylthiophene thiosemicarbazone (2-ATT) and determine their inhibitory study against tyrosinase enzyme. Kinetic studies revealed that, 2-ATT demonstrated a competitive inhibition with Km and Vmax value of 0.056 µM/min and 1.33 min, respectively. In the light of these study, we performed in silico study involving Reduced Density Gradient (RDG), Molecular Electrostatic Potential (MEP), molecular docking and ONIOM (QM/MM) for the 2-ATT with the tyrosinase enzyme. RDG used to find the weak non-covalent interaction (Van der Wall interaction) and strong repulsion (steric effect) of the 2-ATT. MEP and molecular docking were done to identify and investigate the key structural features of 2-ATT that are important for their activity and the interaction that contribute to tyrosinase inhibition respectively. The ONIOM calculations revealed that the binding capacity of control was (5.4 kcal/mol) higher than that of 2-ATT (5.0 kcal/mol), which could explain their difference in their inhibitory behaviour.